The Impact of Sensory; Linguistic and Social Deprivation on Cognition - Matthew Dye (Frontiers Research Topics, 2017)
Early experience plays a crucial role in determining the trajectory of cognitive development. For example, early sensory deprivation is known to induce neural reorganization by way of adaptation to the altered sensory experience. Neville and Bavelier's "compensatory theory'' hypothesizes that loss of one sense may bring about a sensory enhancement in the remaining modalities. Sensory deprivation will, however, also impact the age of emergence, or the speed of acquisition of cognitive abilities that depend upon sensory inputs. Understanding how a child's early environment shapes their cognition is not only of theoretical interest. It is essential for the development of early intervention programs that address not just the early deprivation itself, but also the cognitive sequelae of such deprivation. The articles in this e-book all address different aspects of deprivation - sensory, linguistic, and social - and explore the impacts of such deprivation on a wide range of cognitive outcomes. In reading these contributions, it is important to note that sensory, linguistic, and social deprivation are not independent factors in human experience. For example, a child born deaf into a hearing family is likely to experience delays in exposure to natural language, with subsequent limits on their linguistic competence having an effect on social interactions and inclusion: a child raised in environments where social interaction is highly limited is also likely to experience reductions in the quantity and quality of linguistic inputs. Future work will need to carefully examine the complex interactions between the sensory, linguistic and social environments of children raised in atypical or impoverished environments.